2005
DOI: 10.1080/08989620500217495
|View full text |Cite
|
Sign up to set email alerts
|

Research Misconduct and Crime Lessons from Criminal Science on Preventing Misconduct and Promoting Integrity

Abstract: For 200 years, criminologists theorized that delinquent and criminal acts arise from deviant psychological states (such as irrationality or immorality) and/or social conditions that produce these psychological states. This theoretical perspective, which is being duplicated in most efforts to understand and control research misconduct, has not been productive. More recently, criminological perspectives have emerged, emphasizing situational factors that enhance or restrict the opportunity for illegal or impruden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
2
14
0
3
Order By: Relevance
“…Some authors believe (Stroebe, 2012) that scientists who overstep the mark make a rational decision, weighing up the slim chance of being caught and the limited penalties on the one hand, and the considerable rewards that their inappropriate conduct can bring in terms of prestige, funding, and career advancement on the other hand (Adams and Pimple, 2005). An interesting alternative approach comes from experimental psychology (Ariely, 2012) and is based around the core idea that everyone is inclined to lie and cheat.…”
Section: Researchmentioning
confidence: 99%
“…Some authors believe (Stroebe, 2012) that scientists who overstep the mark make a rational decision, weighing up the slim chance of being caught and the limited penalties on the one hand, and the considerable rewards that their inappropriate conduct can bring in terms of prestige, funding, and career advancement on the other hand (Adams and Pimple, 2005). An interesting alternative approach comes from experimental psychology (Ariely, 2012) and is based around the core idea that everyone is inclined to lie and cheat.…”
Section: Researchmentioning
confidence: 99%
“…Trainees with prior experience and knowledge may reject new ideas about research ethics (McGee et al, 2008). Any misconduct is said to have two elements: propensity and opportunity (Adams and Pimple, 2005). Propensity represents the individual psychological mechanisms that influence self control and rational behavior.…”
Section: Primary Prevention Models "Person Approach" To Primary Prevementioning
confidence: 99%
“…However, criminologists have observed that even when needs are absent and propensity is not fuelled by needs, misconduct can still occur when opportunity for it exists. Modification of opportunities for misconduct at a particular place is deemed to be easier than decreasing propensity (Adams and Pimple, 2005).…”
Section: "Systems Approach" To Primary Preventionmentioning
confidence: 99%
“…Adams and Pimple highlight another avenue on promoting integrity and preventing research misconduct [12]. They posit that responsible conduct of research (RCR) education must focus not only on the development of the researcher's [in this case the trainee's] ethical awareness-the ability to evaluate dilemmas, discuss value choices and develop the self control to resist unethical solutions to research problems-but also on issues of ''opportunity.''…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%